Islamic Transformative Leadership: The Role of School Principals in Encouraging Curriculum Innovation in Islamic-Based Schools - Abidin, Zainal; Qusairi, Ahmad; Wahyudi, Iqmal (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
This study aims to examine in depth the role of the principal in implementing Islamic Transformative Leadership to encourage curriculum innovation at SMPN 4 Bangil, Pasuruan, while also emphasizing its significant contributions and implications for the development of character-based, innovative Islamic education. A qualitative approach with a case study method was used to gain a comprehensive understanding through in-depth interviews and direct observation over two months (February-March 2025). The study participants consisted of the principal and 10 teachers, who were purposively selected based on their experience, active involvement, and knowledge of the innovation process in the school. Data were collected through semi-structured interviews and documentation of school activities, and then analyzed thematically to identify patterns and relationships between Islamic leadership strategies, organizational culture, and the success of curriculum innovation. The results show that the principal plays a central role as an inspiration, role model, and motivator in instilling Islamic values ​​, such as justice, sincerity, and morality, across all aspects of school activities, thereby increasing active teacher participation in curriculum innovation by up to 90%. Teacher empowerment strategies, effective communication, and the instilling of moral values are the main factors supporting the success of Islamic-based innovation. These findings provide practical recommendations for educational leaders to adopt Islamic Transformative Leadership as an essential leadership model in creating a resilient, innovative, and character-driven Islamic school ecosystem, thereby strengthening the quality and relevance of Islamic education in the future.